Place Spirituality: An attachment perspective - Counted, Victor (Archive for the psychology of religion, 2019)
The expression of attachment to the divine in certain places among different groups has been documented by anthropologists and sociologists for decades. However, the psychological processes by which this happens are not yet fully understood. This article focuses on the concept of ‘place spirituality’ as a psychological mechanism, which allows the religious believer or non-believer to achieve an organised attachment strategy, involving the interplay of place and spiritual attachment. First, place spirituality is considered as an experience that satisfies the attachment relationship criteria in that geographic places and divine entities can be perceived as ‘objects’ of attachment. Second, it is proposed that the maturational aspects of the attachment repertoire in adults make the place spirituality experience possible since adults’ cognitive abilities are much wider than those of children and can include relationships to geographical spaces and invisible divine entities. Finally, the theme of place spirituality is explored to further position the concept as a relational paradigm for understanding the relationship between place experiences and spiritual attachment.